Celebrification Process of Celebrity Children on TikTok: A Study on Media Exposure, Personal Characteristics, and Public Engagement - Azhar, Muchammad Jiddan; Aesthetika, Nur Maghfirah (CHANNEL: Jurnal Komunikasi, 2024)
The development of information technology has transformed the way humans communicate and interact, with social media platforms like TikTok becoming an essential part of daily life. This research focuses on the phenomenon of the celebrification of celebrity children on TikTok, examining how the children of famous celebrities such as Rayyanza Malik Ahmad, Bilqis Khumairah Razak, and Gala Sky Ardiansyah gain popularity on the platform. The study employs micro-celebrity theory and the concept of celebrification as its theoretical framework. The research method used is netnography with a qualitative approach, collecting data through a literature review and content analysis of TikTok videos. The findings indicate that the process of celebrification of celebrity children on TikTok is driven by high media exposure, unique personal characteristics, skills in creating engaging content, and popularity measured by the number of followers, likes, and other interactions. This study suggests the importance of further understanding the impact of celebrification on the development of celebrity children and the potential broader social implications.